2013
DOI: 10.1177/0002764213515226
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Political and Civic Engagement Among Youth During the 2012 Presidential Campaign

Abstract: A national mail survey of adolescents between the ages of 12 and 17 ( n = 876) was conducted immediately before the U.S. presidential election (October 2012) to investigate socialization agents that may correlate with political and civic engagement. The relative importance of potential correlates of engagement including demographics, parents, peers, schools, religion, traditional media, social networks, and digital communication were evaluated. Regression analysis revealed that civically engaged youth identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 57 publications
(107 reference statements)
1
26
0
Order By: Relevance
“…Unlike participatory citizens or justice-oriented citizens, the students in this study represent a conventional notion of citizenship; they possess a sense of duty but lack willingness or ability to engage in the political process (Dalton, 2008). Whereas conventional perspectives on citizenship involve party identification, awareness of issues, and political discussion (Reichert, 2016b), political engagement involves "efforts to affect policy, politics, and institutions of government" (Wicks, Wicks, Morimoto, Maxwell, & Schulte, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike participatory citizens or justice-oriented citizens, the students in this study represent a conventional notion of citizenship; they possess a sense of duty but lack willingness or ability to engage in the political process (Dalton, 2008). Whereas conventional perspectives on citizenship involve party identification, awareness of issues, and political discussion (Reichert, 2016b), political engagement involves "efforts to affect policy, politics, and institutions of government" (Wicks, Wicks, Morimoto, Maxwell, & Schulte, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The teachers in the study can be commended for igniting students' interest in and focus on the election, which relates to (Sears & Valentino, 1997) impressionable years hypothesis. However, in order move students' interest to actionable engagement in the political system, the teachers should teach the students about actions they can take, such as writing to their political representatives, attending rallies and town hall meetings, boycotting, and even participating in online communities (Reichert, 2016a;Wicks et al, 2014). When students feel a sense of belonging and connectedness, they are more likely to "act on behalf of a common good" .…”
Section: Discussionmentioning
confidence: 99%
“…Hanks analyzed such ways of political participation as discussion of the issues, campaign participation, and voting. Since that research, study of the relation between participation in voluntary organizations and participation in political activities in adulthood has been developed by many scientists (Wicks et al 2014). Andolina et al (2002) found that participants of their research 'included a wide range of activities under the rubric of volunteering, many of which fall outside the boundaries of traditional definitions.…”
Section: Literature Review Of Determinants and Predictors Of Politicamentioning
confidence: 99%
“…The purpose of this study is to investigate how the civic potential of the rapidly growing immigrant student population in the U.S. may or may not be realized in the current social studies context. We define civic potential as an individual’s, or group of individuals’, likelihood of developing into citizens who are informed and engaged in both the political and civic life of the community (Wicks et al, 2014). We position these citizens similarly to Westheimer & Kahne’s (2004) participatory citizen.…”
mentioning
confidence: 99%
“…We position these citizens similarly to Westheimer & Kahne’s (2004) participatory citizen. Further, for our purposes and consistent with Wicks et al (2014), we define political engagement as participation in and with political institutions, including voting, for the purpose of influencing public policy. Civic engagement includes community involvement beyond the political dimension (i.e., volunteerism, fundraising, services designed to better the community (p. 624)).…”
mentioning
confidence: 99%